Does anticholinergics drug burden relate to global neuro-disability outcome measures and length of hospital stay?. (15th October 2015) - Sakel, M.; Boukouvalas, A.; Buono, R.; Moten, M.; Mirza, F.; Chan, W.-Y.; Maidment, I.; Cross, J.; Smith, T. O.; Myint, P. K.; Fox, C.
Abstract: Primary objective : To assess the relationship between disability, length of stay (LOS) and anticholinergic burden (ACB) with people following acquired brain or spinal cord injury. Research design : A retrospective case note review assessed total rehabilitation unit admission. Methods and procedures : Assessment of 52 consecutive patients with acquired brain/spinal injury and neuropathy in an in-patient neuro-rehabilitation unit of a UK university hospital. Data analysed included: Northwick Park Dependency Score (NPDS), Rehabilitation complexity Scale (RCS), Functional Independence Measure and Functional Assessment Measure FIM-FAM (UK version 2.2), LOS and ACB. Outcome was different in RCS, NPDS and FIM-FAM between admission and discharge. Main outcomes and results : A positive change was reported in ACB results in a positive change in NPDS, with no significant effect on FIM-FAM, either Motor or Cognitive, or on the RCS. Change in ACB correlated to the length of hospital stay (regression correlation = −6.64; SE = 3.89). There was a significant harmful impact of increase in ACB score during hospital stay, from low to high ACB on NPDS (OR = 9.65; 95% CI = 1.36–68.64) and FIM-FAM Total scores (OR = 0.03; 95% CI = 0.002–0.35). Conclusions : There was a statistically significant correlation of ACB and neuro-disability measures and LOS amongst this patient cohort.